Uzbek Teachers’ Digital Competence in Remote English Language Teaching for Non-Linguistic Majors - Ruzmetova , Sohiba (The Lingua Spectrum, 2025)
This article examines how teachers’ digital competence affects remote English language teaching for non-linguistic majors in higher education. We focus on the key dimensions of digital competence in this context – including the use of learning platforms, online assessment tools, and communication technologies – and how these influence teaching practices and student outcomes. Employing a mixed – methods approach, the study surveyed 100 teachers and conducted interviews with 30 participants. We also identify the challenges teachers face in developing and applying digital competence (e.g. lack of training, resistance to technology, maintaining student engagement, the digital divide especially in rural areas) and propose realistic, evidence-based solutions. The study also examines the relationship between teachers’ digital competence, their academic qualifications, and teaching experience, noting higher competence among doctoral degree holders and mid – career teachers. By drawing on recent empirical studies and educational reports, our aim is to provide a comprehensive analysis that can inform professional development and policy efforts to enhance digital competence among language instructors in non-linguistic faculties.